PENERAPAN TERAPI RELAKSASI BENSON UNTUK MENURUNKAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI KELUARGA WILAYAH BINAAN PUSKESMAS PEGANDAN SEMARANG - Margiyati Margiyati; Anggrai Putri Setyajati (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
Hypertension is an increase in blood pressure above normal which has a very close relationship with the elderly, so it can cause complications and cardiovascular disease if not treated properly. In the treatment of hypertension, the elderly can control blood pressure by using the Benson relaxation technique. Benson relaxation is a non-pharmacological therapy that uses the breathing relaxation method by involving the patient's belief factor. This case study aims to describe the application of Benson relaxation therapy 10-15 minutes, 2 times a day, for 3 days can reduce blood pressure in the elderly with hypertension in the Pegandan Public Health Center Semarang. The type of case study used is descriptive. The subjects used were 2 people with criteria of age > 60 years, BP 140/90 mmHg – 159/99 mmHg. The instrument used is a digital sphygmomanometer and Benson relaxation SOP. The final result of the application of Benson relaxation showed that subject I experienced a decrease in blood pressure on the first day, namely 158/92 mmHg to 138/84 mmHg on the third day, subject II experienced a decrease in blood pressure on the first day, namely 158/86 mmHg to 130/76 mmHg on the third day. The level of family independence of the two subjects increased from the level of independence of III to IV. Benson relaxation is recommended to help lower blood pressure in the elderly with hypertension